Development of a Joyful Learning-Based Instructional Model in Javanese Script - Sukoyo, Joko; Kurniati, Endang; Utami, Esti Sudi (JOLLT Journal of Languages and Language Teaching, 2024)
Learning Javanese script is considered an outdated and boring lesson. This paradigm of boring and obsolete Javanese script lessons must be changed into a modern, interesting, and enjoyable learning experience. One way to do this is by developing a Joyful Learning-based model for Javanese language instruction. Joyful Learning is a concept of enjoyable learning. The development of a Joyful Learning-based model for Javanese language instruction is urgent and necessary because the learning model currently used by students needs to employ the principles of Joyful Learning, resulting in students feeling bored, tired, and unmotivated to learn. Additionally, Javanese language instruction is viewed as a good means to develop the character of the nation’s children, as it contains values of morality and politeness. The research design used is the ADDIE Research and Development design, with the steps of analyzing, designing, developing, implementing, and evaluating. This study uniquely integrates traditional games into the Joyful Learning model. The result of the study is creating a Joyful Learning-based model for Javanese script instruction. The components of this model include the social system, reaction principles, support system, instructional and incidental impacts, and syntagmatic. The syntagmatic model of Joyful Learning-based Javanese script instruction includes an introduction, material delivery, games for writing sentences, games for reading paragraphs in Javanese script, formative assessment, and reflection. The learning model has been tested at SMPN 12 Semarang. The results of the school trial indicate that the Joyful Learning-based Javanese script instruction model is effective for learning.